Experiential learning in psychotherapy: ropes course exposures as an adjunct to inpatient treatment - Wolf, Markus; Mehl, Kilian (Clinical psychology & psychotherapy, 2011)
Exposures to a high-ropes course are introduced as an adjunct intervention in the therapy of psychotherapy patients. A controlled study was conducted to investigate the effectiveness of high-ropes exposures as an add-on to inpatient treatment in a naturalistic setting. In a sample of 247 patients, depressive symptoms, trait anxiety, locus of control and self-efficacy were assessed at admission and discharge of treatment and at 24-month follow-up. Follow-up data were available for 104 patients who attended the ropes courses and 53 control patients who underwent an inpatient treatment programme as usual. At the end of treatment, more high-rope participants showed clinically significant change on trait anxiety than controls but not regarding depressive symptoms. High-rope participants showed better follow-up outcomes than controls in trait anxiety and self-efficacy but not in depressive symptoms and external locus of control. Moreover, during follow-up, in the high-rope group, more patients showed reliable improvements and fewer patients showed reliable deteriorations in trait anxiety as compared with controls. The study gives a preliminary indication that the high-rope interventions are a feasible and valuable add-on to inpatient psychotherapy. The study design, sample composition and loss to follow-up are discussed as potential limitations of the study. Copyright © 2010 John Wiley & Sons, Ltd. Key Practitioner Message: • Based on the principles of experiential learning, outdoor ropes courses are a means for the facilitation of personal growth and promotion of individual coping skills. • A ropes course intervention was evaluated as an add-on to a psychotherapy inpatient programme. • In a diagnostically mixed inpatient sample, participation in ropes course exposures seemed to be related with better long-term outcomes on personality variables—trait anxiety and self-efficacy—but not regarding depressive symptoms and state anxiety. • Interventions that draw upon experience and group action might be a valuable addition to talking psychotherapy.